Optimal receiver and blind demodulation performance bounds for single channel co-frequency mixed signals - YU Hongyi; ZHA Renpeng; SHEN Zhixiang; SHEN Caiyao; HU Yunpeng (Tongxin xuebao)
Aiming at the problem of optimal detection of mixed signal symbol sequences, on the basis of co-frequency mixed receiving baseband signal model, sufficient statistics for joint maximum likelihood blind detection were derived, and the optimal receiver design of “mixed waveform matched filtering and symbol rate dual sampling” was given. Based on the sufficient statistics model, a lower bound on the performance of single-channel blind demodulation for co-frequency mixed signals was derived using Forney’s method. Since the complexity of the optimal receiver grows exponentially with the equivalent symbol rate sampling channel length, the impact of the truncation error on the blind demodulation performance was further analyzed for the channel truncation problem in practical applications. The result shows that the simulation results of the optimal receiver coincide with the theoretical performance analysis results, verifying the reasonableness of the derived performance bounds.